UNIFICATION OF SIMPLIFIED PROCEEDINGS IN CIVIL AND ECONOMIC PROCEDURAL LAW (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Abstract The article examines simplified proceedings in civil and economic procedural law of Uzbekistan, focusing on reforms introduced in 2019 (Economic Procedural Code) and 2021 (Civil Procedural Code). Key differences between the codes are analyzed: while the EPC explicitly excludes corporate disputes and legal sanctions from simplified procedures, the CPC lacks such limitations. The author emphasizes disparities in claim thresholds (e.g., 10x vs 5x base calculation amount for individual entrepreneurs) and procedural deadlines (15-day response time under EPC vs undefined terms in CPC), arguing for legislative unification to ensure consistency. The study concludes that harmonizing these norms would enhance legal predictability, reduce litigation costs, and strengthen trust in the judicial system, particularly for SMEs and entrepreneurs.